Value of shoulder US compared to MRI in infants with obstetric brachial plexus paralysis - Gunes, Altan (Diagn Interv Radiol, 2021)
PURPOSE: Children with brachial plexus birth injury (BPBI) may eventually develop glenohumeral instability due to development of unbalanced muscular strength. Our major goal in this study is to compare the accuracy of physical examination and ultrasonography (US) in determination of glenohumeral instability in infants with BPBI compared with magnetic resonance imaging (MRI) as a gold standard, and to investigate the role and value of US as a screening modality for assessing glenohumeral instability. METHODS: Forty-two consecutive patients (mean age, 2.3±0.8 months) with BPBI were enrolled into this prospective study. Patients were followed up with physical examination and US with dynamic evaluation in 4–6 weeks intervals. Patients who developed glenohumeral instability based on physical examination and/or US (n=21) underwent MRI. Glenohumeral instability was defined as alpha angle >30° and percentage of posterior humeral head displacement >50%. Diagnostic accuracy of physical examination and US was calculated and quantitative parameters were compared with Wilcoxon test. RESULTS: Glenohumeral instability was confirmed with MRI in 15 of 21 patients. Accuracy and sensitivity of physical examination and US were 47%, 66% and 100%, 100%, respectively in determination of glenohumeral instability. No significant difference was found for the alpha angle (p = 0.173) but the percentage of posterior humeral head displacement was statistically significant between US and MRI (p = 0.028). CONCLUSION: Our results indicate that US with dynamic evaluation is a good alternative for MRI in assessment of glenohumeral instability in infants with BPBI, since it is highly accurate and specific, and quantitative measurements used for glenohumeral instability were comparable to MRI. US can be used as a screening method to assess glenohumeral instability in infants with BPBI.